Phase II study evaluating the association of gemcitabine, trastuzumab and erlotinib as first‐line treatment in patients with metastatic pancreatic adenocarcinoma (GATE 1). Issue 3 (2nd September 2020) - Assenat, Eric; Mineur, Laurent; Mollevi, Caroline; Lopez‐Crapez, Evelyne; Lombard‐Bohas, Catherine; Samalin, Emmanuelle; Portales, Fabienne; Walter, Thomas; de Forges, Hélène; Dupuy, Marie; Boissière‐Michot, Florence; Ho‐Pun‐Cheung, Alexandre; et al.
Abstract: In a previous phase II study (THERAPY), cetuximab and trastuzumab combination, as second‐line after progression with gemcitabine, showed disease stabilization in 27% of 33 patients with pancreatic carcinoma. In the present phase II multicenter study, we assessed the efficacy and tolerance of gemcitabine, trastuzumab plus erlotinib as first‐line treatment of metastatic pancreatic cancer. The primary endpoint was disease control rate (DCR, RECIST v.1); secondary endpoints were progression‐free (PFS), overall (OS) survival and toxicity (NCI‐CTCAE v3.0). Ancillary study addressed the predictive value of both EGFR/HER2 expression and KRAS mutational status. Sixty‐three patients from four centers were included (62 evaluable for toxicity, 59 for efficacy), median age was 62 years (35‐77), 59.7% men. The median treatment duration was 16.1 weeks (2.1‐61). Eleven patients (19%) reported a partial tumor response, and 33 (56%) disease stabilization. DCR was 74.6% (95%CI: 61.8‐85.0; 44/59 patients). After a median follow‐up of 23.3 months (0.6‐23.6), median PFS was 3.5 months (95%CI: 2.4‐3.8) and median OS 7.9 months (95%CI: 5.1‐10.2). PFS was significantly longer in patients with grade ≥ 2 cutaneous toxicities vs patients with grade 0‐1 toxicities (HR = 0.55, 95%CI: 0.33‐0.92, P = .020). Expression of EGFR and HER2 was correlated with PFS and OS in multivariate analysis; HER2 expression was correlated with the tumor response. Main severe toxicities were neutropenia (32%), cutaneous rash (37%) and thrombosis/embolisms (35.5%). This triplet combination is effective in terms of disease control, PFS and OS, and acceptable for safety. A larger study to investigate this combination compared to the standard regimen should be discussed. Abstract : What's new? Despite extensive investigation into gemcitabine‐based combination therapies for pancreatic cancer, significant need remains for novel strategies with improved clinical benefit. A promising approach is the triplet combination gemcitabine, trastuzumab, and erlotinib, which the present pilot multicenter phase II trial identifies as an effective strategy for disease control and survival when used as a first‐line regimen. In particular, pancreatic cancer patients with grade 2 or worse cutaneous toxicity showed superior progression‐free survival compared to patients with grade 0‐1 cutaneous toxicities. In multivariate analyses, progression‐free and overall survival were correlated EGFR and HER2, while HER2 expression was linked to tumor response.